District-wide outcomes from a bullying prevention programming. Issue 3 (5th July 2022) - McDaniel, Sara C.; Nese, Rhonda N. T.; Tomek, Sara; Jiang, Shan
Abstract: Bullying in schools contributes to peer conflict, disruptive behavior, internalized victimization, and many other deleterious outcomes for students. This study examined the integration of a schoolwide bullying prevention intervention in a pre/post design comparing grade level aggregated data for elementary, middle, and high school across two timepoints. Results demonstrate that differences in response to bullying prevention occur across the two time points for each grade level. The greatest positive change was found for middle school students, indicating that bullying prevention could most effectively be delivered in middle school. Lack of significant changes may indicate that interventions may require more than one year, that the baseline scores were too high to detect significant change, or measures were not sensitive enough to detect change.